AN ERROR ANALYSIS OF SOME ESSAYS WRITTEN BY THE STUDENTS OF ENGLISH EDUCATION STUDY PROGRAM GUNUNG RINJANI UNIVERSITY - MAWARDI (LPPM Universitas Gunung Rinjani, 2020)
The purpose of the present study is to know the types and factors of errors encountered by the students in writing essay of various types. This research was designed as descriptive qualitative research. The subjects of the study were the fifth semester students of English Education Department of Gunung Rinjani University who are taking Writing course. The study followed qualitative approach with case study design. The data were collected from test, questionnaire, and documentation. The essays were analyzed based on the steps of error analysis: identification of error, explanation of error, description of error, and evaluation of the error. Data from interview were analyzed using Mile and Huberman’s model of analysis. While the data collected through questionnaire were analyzed to support the interpretation on the cause of errors. The study shows that types of errors in the students essays are: Grammatical Error (30%), Mechanic Error (25%), Stylistic Error (20%), Lexical Error (15%), and Organization Error (10%); 2) factors that cause the students to commit errors are: a) Interference/Language Transfer, b) Intralingual Error (Overgeneralization, Ignorance Rule of Restriction, Incomplete Application of Rules, and Semantic error), c) Lack of Motivation, and d) Limited Exposure to the Target Language. This study suggest the English lecturers to apply error analysis as the technique in teaching writing in the classroom setting.Keywords: Student Error, Student Essay WritingTujuan dari penelitian ini adalah untuk mengetahui jenis dan faktor kesalahan yang ditemui oleh siswa dalam penulisan esai berbagai jenis. Penelitian ini dirancang sebagai penelitian deskriptif kualitatif. Subjek penelitian adalah siswa semester lima Jurusan Pendidikan Bahasa Inggris Universitas Gunung Rinjani yang mengikuti kursus Penulisan. Penelitian ini mengikuti pendekatan kualitatif dengan rancangan studi kasus. Data dikumpulkan dari tes, kuesioner, dan dokumentasi. Esai dianalisis berdasarkan langkah-langkah analisis kesalahan: identifikasi kesalahan, penjelasan kesalahan, deskripsi kesalahan, dan evaluasi kesalahan. Data dari wawancara dianalisis dengan menggunakan model analisis Mile dan Huberman. Sedangkan data yang dikumpulkan melalui kuesioner dianalisis untuk mendukung interpretasi penyebab kesalahan. Kesalahan Gramatikal (30%), Kesalahan Mekanik (25%), Kesalahan Gaya (20%), Kesalahan Leksikal (15%), dan Kesalahan Organisasi (10%); 2) faktor-faktor yang menyebabkan siswa melakukan kesalahan adalah: a) Interferensi / Transfer Bahasa, b) Kesalahan Intralingual (Overgeneralisasi, Ketidaktahuan Aturan Pembatasan, Aturan Aturan yang Tidak Lengkap, dan Kesalahan Semantik), c) Kurangnya Motivasi, dan d) Terbatasnya Eksposur terhadap Bahasa Target. Studi ini menyarankan para dosen untuk menerapkan analisis kesalahan sebagai teknik dalam mengajar menulis di kelas.Kata kunci : Kesalahan siswa, penulisan esai siswa